Structural, Syntactic, and Statistical Pattern Recognition Joint IAPR International Workshop, SSPR & SPR 2008, Orlando, USA, December 4-6, 2008. Proceedings - Vitoria Lobo, Niels da.; Kasparis, Takis; Roli, Fabio; Kwok, James T.; Georgiopoulos, Michael; Anagnostopoulos, Georgios C.; Loog, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the refereed proceedings of the 12th International Workshop on Structural and Syntactic Pattern Recognition, SSPR 2008 and the 7th International Workshop on Statistical Techniques in Pattern Recognition, SPR 2008, held jointly in Orlando, FL, USA, in December 2008 as a satellite event of the 19th International Conference of Pattern Recognition, ICPR 2008. The 56 revised full papers and 42 revised poster papers presented together with the abstracts of 4 invited papers were carefully reviewed and selected from 175 submissions. The papers are organized in topical sections on graph-based methods, probabilistic and stochastic structural models for PR, image and video analysis, shape analysis, kernel methods, recognition and classification, applications, ensemble methods, feature selection, density estimation and clustering, computer vision and biometrics, pattern recognition and applications, pattern recognition, as well as feature selection and clustering.
Invited Talks (Abstracts) -- SSPR -- Poster Papers -- SPR -- Poster Papers -- Invited Talks (Full Papers).
Keywords: Computer science; Computers; Computer science -- Mathematics; Mathematical statistics; Image processing; Pattern recognition; Application software; Computer Science; Pattern Recognition; Theory of Computation; Computer Applications; Discrete Mathematics in Computer Science; Probability and Statistics in Computer Science; Image Processing and Computer Vision; Electronic books